# To find sum of three numbers 14,27 and 13 , we can have two ways:(a) We may first add 14 and 27 to get 41 and then add 13 to it to get the total sum 54 or(b) We may add 27 and 13 to get 40 and then add 14 to get the sum 54 . Thus, $(14+27)+13=14+(27+13)$This can be done for any three numbers. This property is known as the associativity of addition of numbers. Express this property which we have already studied in the chapter on Whole Numbers, in a general way, by using variables $a, b$ and $c$.

#### Complete Python Prime Pack

9 Courses     2 eBooks

#### Artificial Intelligence & Machine Learning Prime Pack

6 Courses     1 eBooks

#### Java Prime Pack

9 Courses     2 eBooks

To do:

We have to express the given property in a general way, by using variables $a, b$ and $c$.

Solution:

$(14+27)+13=41+13=54$

$14+(27+13)=14+40=54$

Let $a=14, b=27, c=13$

This implies,

$(a+b)+c=a+(b+c)$

Therefore,

For any three whole numbers $a, b$ and $c$

$(a + b) + c = a + (b + c)$

Updated on 10-Oct-2022 13:36:46